Morphological and functional decline of the SNc in a model of progressive parkinsonism - Jacob M. Muñoz; John T. Williams; Joseph J. Lebowitz (npj Parkinson's Disease)
Abstract The motor symptoms of Parkinson’s Disease are attributed to the degeneration of dopamine neurons in the substantia nigra pars compacta (SNc). Previous work in the MCI-Park mouse model has suggested that the loss of somatodendritic dopamine transmission predicts the development of motor deficits. In the current study, brain slices from MCI-Park mice were used to investigate dopamine signaling in the SNc prior to and through the onset of movement deficits. Electrophysiological properties were impaired by p30 and somatic volume was decreased at all time points. The D2 receptor activated potassium current evoked by quinpirole was present initially, but declined after p30. In contrast, D2-IPSCs were absent at all time points. The decrease in GPCR-mediated inhibition was met with increased spontaneous GABAA signaling. Dendro-dendritic synapses are identified as an early locus of dysfunction in response to bioenergetic decline and suggest that dendritic release sites may contribute to the induction of degeneration.